In vivo study of Centella asiatica leaf extract cream for Matrix Metalloproteinase-1 inhibition and collagen enhancement to prevent photoaging - Purmawanti, Sri; W, Joko Wahyu; Sumarawati, Titiek (Universitas Muhammadiyah Purwokerto, 2025)
Background: Ultraviolet B (UVB) exposure accelerates skin aging, causing wrinkles and increasing matrix metalloproteinase-1 (MMP-1) activity, which degrades collagen. Centella asiatica (CA) has well-documented anti-inflammatory and antioxidant properties that may counteract UVB-induced photoaging. However, studies on its topical formulation for MMP-1 inhibition and collagen enhancement remain limited.Purpose: This study aims to determine the effect of CA leaf extract cream on inhibiting MMP-1 and increasing collagen in skin tissue exposed to UVB rays.Methods: This experimental study used a post-test only control group design. The sample population of BALB/c mice was 24, divided into four groups: healthy control group (KN), negative control group (K-), Treatment 1 (P1): 10% CA extract cream dosage, and Treatment 2 (P2): 20% CA extract cream dosage. Skin tissue samples were measured for MMP-1 expression using immunohistochemistry (IHC) staining, and collagen density using Sirius Red staining. Data analysis on MMP-1 expression using One-way ANOVA test and collagen density using Kruskal Wallis test.Results: MMP-1 expression was highest in the K2 group (UVB exposure + cream base) and decreased in the P1 and P2 groups (10% CA cream), with the lowest expression in the K1 group (healthy control). However, One-Way ANOVA showed no significant differences among groups (p=0.053). Collagen density analysis using the Kruskal-Wallis test showed significant differences (p = 0.04), with a decrease in the K2 group and an increase in the K3 and K4 groups.Conclusion: Application of CA extract cream affects MMP-1 expression and collagen density in skin tissue exposed to UVB rays.